2022
DOI: 10.3389/fgene.2022.836853
|View full text |Cite
|
Sign up to set email alerts
|

Paternal De Novo Variant of TAOK1 in a Fetus With Structural Brain Abnormalities

Abstract: A dilated lateral ventricle is a relatively common finding on prenatal ultrasound, and the causes are complex. We aimed to explore the etiology of a fetus with a dilated lateral ventricle. Trio whole-exome sequencing was performed to detect causative variants. A de novo variant of TAOK1 (NM_020791.2: c.227A>G) was detected in the proband and evaluated for potential functional impacts using a variety of prediction tools. Droplet digital polymerase chain reaction was used to exclude the parental mosaicism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…A recent report of a de novo frameshift variant in a girl with isolated childhood-onset tremor was also excluded, because, based on the available clinical data, she did not properly fit into the definition of NDD [ 22 ]. Prenatal cases were also excluded [ 17 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent report of a de novo frameshift variant in a girl with isolated childhood-onset tremor was also excluded, because, based on the available clinical data, she did not properly fit into the definition of NDD [ 22 ]. Prenatal cases were also excluded [ 17 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Yu et al recently reported one case of brain MRI abnormalities in a fetus with a de novo missense TAOK1 variant, in which bilateral polymicrogyria of the lateral fissure area could not be ruled out by the authors [ 18 ]. It would be interesting to know whether a postnatal MRI would confirm a malformation of cortical development.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation